1997
DOI: 10.1074/jbc.272.3.1735
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted Laser Desorption Ionization/Quadrupole Ion Trap Mass Spectrometry of Peptides

Abstract: The polymerase-associated phosphoprotein (P protein) from Sendai virus, a murine Paramyxovirus, is reported in the literature to be a highly phosphorylated protein. In vitro studies have detected phosphorylation in different regions of the protein, while a single phosphopeptide (identified as the sole phosphorylation) site) was observed using in vivo techniques. In this work, two phosphorylation sites of the P protein from Sendai virus are localized by a direct approach using matrix-assisted laser desorption i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Qin and et al 13. used preferential fragmentation at the C‐terminus of Asp and Glu residues as markers to help validate sequence assignments, while Jonscher and Yates14 were able to localize phosphorylated residues using fragment ions inadvertently generated in the source. Although source fragmentation has provided useful information, improved determination of post‐translational modifications may be possible by capitalizing instead on the MS n capability of ion traps.…”
mentioning
confidence: 99%
“…Qin and et al 13. used preferential fragmentation at the C‐terminus of Asp and Glu residues as markers to help validate sequence assignments, while Jonscher and Yates14 were able to localize phosphorylated residues using fragment ions inadvertently generated in the source. Although source fragmentation has provided useful information, improved determination of post‐translational modifications may be possible by capitalizing instead on the MS n capability of ion traps.…”
mentioning
confidence: 99%
“…As a consequence, under typical operating conditions, only a single stage of tandem mass spectrometry may be available using these techniques, limiting their scope for the analysis of complex oligosaccharides. In contrast, it has been demonstrated that the quadrupole ion trap is a useful tool for the analysis of biomolecules such as peptides,31–33 oligonucleotides34,, 35 and oligosaccharides,13,, 14 through the use of successive stages of trapping and CAD to reveal structural details that cannot be resolved by MS/MS alone.…”
mentioning
confidence: 99%
“…Phosphopeptides have also been detected and assigned for modification sites in the course of vacuum or atmospheric pressure MALDI-ion trap-MS experiments [145,148]. In addition to pSer and pThr residues, unexpected elimination of the elements of H 3 PO 4 from pTyr-containing phosphopeptides was also observed under atomospheric pressure ionization conditions [149].…”
Section: Collision-induced Dissociationmentioning
confidence: 95%